PENGARUH KEPERCAYAAN DAN KEPUASAN KONSUMEN TERHADAP MINAT BELI PADA SITUS BELANJA ONLINE SHOPEE DI BATAM - Reny Br Surbakti; Winda Evyanto (STIE Wiyatamandala, 2023)
The purpose of this study aims to analyze the influence of consumer trust and satisfaction on the intention to buy online Shopee in Batam. The analytical method used by the author is to use quantitative research with a total of 147 respondents who are residents of Batu Aji, Batam city. In collecting the data, it is done bydistributing questionnaires in which there are several statement items. In this study, the variables were divided into several parts, including consumer trust and satisfaction as independent variables, and purchase intention as the dependent variable. To measure the magnitude of the influence on these variables, the authorsuse the method of linear regression analysis and multiple regression. From the results of the analysis it was found that partially trust has no effect on purchase intention, customer satisfaction partially has an influence on purchase intention. The variables of consumer trust and satisfaction have a simultaneous influence on the intention to buy online shops in Batam